Student attitudes on the use of L1 in upper secondary ESL classroom / Nuruladilah Mohamed - Mohamed, Nuruladilah (2011)
Research and studies in the area of student attitudes towards the use of first language (L1) which is Bahasa Melayu, in the ESL classroom provide significant insights and suggestions to teachers and curriculum designers in improving the language learning environment and performance of the students. The study was conducted to investigate the high and low level student attitudes on the use of L1 in the ESL classroom. This study thus adopted the survey questionnaire developed by Oliver Rose in 2007. The findings of the study indicated that the high level students have positive affection towards second language (L2) more than the low level students. Besides, the high level students expected to have maximum exposure of L2 in the learning time while the low level students expected to be assisted by L1 in their learning time. Furthermore, the study also proven that the students’ affective filters influenced their attitudes on the learning experience in the ESL classrooms. In addition, the differences of the attitudes between two proficiency levels were also reflected their preferences towards the teaching approaches either to use L1 or L2 in the teaching time. Hence, English language teachers should be aware of the attitudes among the ESL students regardless of the students’ proficiency levels and match their teaching approaches with the learning preferences as well as the student attitudes to help improve the students’ competence in the English language classrooms.